Musik til shoppere - Christina Ranum; Nicolai J. Graakjær (Akademisk Kvarter, 2012)
Christina Ranum and Nicolai J. Graakjær Musik til shopper En empirisk undersøgelse af kunders opfattelse af butikmusik. (Music for shoppers An empirical examination of customers' views of music in shops). Increasingly shops need branding. Music can be important in this connection, and earlier research has indicated that music creates atmosphere and meaning, and that music can even influence the consumer's choice of products. However, research has been characterized by a predominantly quantitative, experimental approach, and there are no independent research studies of shop music in a Danish context. In this way the article supplements existing research by its examination of the meaning of shop music in a Danish context using qualitative methods. Referring to a selected shop environment (The Salling department store in Aalborg) it presents, discusses and puts the result of 126 "exit interviews" as well as a more extensive focus group survey into perspective.